Forms of Language Units and Meanings of Hamlet Toponymy in Labuhan Haji Village, West Nusa Tenggara - Sasmayunita, Sasmayunita; Hilmi, Hubbi Saufan; Setiyoningsih, Titi; Thahir, Asriani (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Toponymy or place naming not only functions as a location marker, but also represents a community's linguistic structure and cultural values. However, studies on toponymy at the dusun level, especially in Labuhan Haji Village, Labuhan Haji Sub-district, East Lombok Regency, are still minimal. This study aims to describe the form of linguistic units and the meaning of toponymy of hamlets in the Region. The method used is descriptive qualitative with an anthropological approach, which combines structural linguistic analysis and cultural meaning studies. Data were obtained through in-depth interviews, participatory observation, and oral and visual documentation, which were then analyzed using morphological and semantic models. The results show that the names of hamlets are formed through complex linguistic units, such as affixation, reduplication, and compositum, which represent geographical conditions, historical events, and symbolic values of the Sasak people. Each toponymy contains layers of meaning that are not only descriptive but also functional in maintaining the local community's collective memory, social structure, and cultural identity. This research provides theoretical contributions to the development of formal and contextual linguistics-based toponymy studies and practical contributions in preserving intangible cultural heritage through language documentation. The findings also open up space for the development of a low-content curriculum.